EFFECT OF THAI SARAPHI FLOWER EXTRACTS ON WT1 AND BCR/ABL PROTEIN EXPRESSION IN LEUKEMIC CELL LINES - Rungkarn Sangkaruk (2018)
BACKGROUND: Saraphi (Mammea siamensis) is a Thai traditional herb. In this study, the cytotoxic effects of crude ethanolic and fractional extracts including hexane, ethyl acetate, and methanol fractions from M. siamensis flowers were investigated in order to determine their effect on WT1 expression in Molt4 and K562 cells and Bcr/Abl expression in K562 cells. MATERIALS AND METHODS: The flowers of M. siamensis were extracted using ethanol. The ethanol flower extract was further fractionated with hexane, ethyl acetate, and methanol. Cytotoxic effects were measured by the MTT assay. Bcr/Abl and WT1 protein levels after treatments were determined by Western blotting. The total cell number was determined via the typan blue exclusion method. RESULTS: The hexane fraction showed the strongest cytotoxic activity on Molt4 and K562 cells, with IC50 values of 2.6 and 77.6 μg/ml, respectively. The hexane extract decreased Bcr/Abl protein expression in K562 cells by 74.6% and WT1 protein expressions in Molt4 and K562 cells by 68.4 and 72.1%, respectively. Total cell numbers were decreased by 66.2 and 48.7% in Molt4 and K562 cells, respectively. Mammea E/BB (main active compound) significantly decreased both Bcr/Abl and WTlprotein expressions by 75 and 49.5%, respectively when compared to vehicle control. CONCLUSION: The hexane fraction from M. siamensis flowers inhibited cell proliferation via the suppression of WT1 expression in Molt4 and K562 cells and Bcr/Abl expression in K562 cells. The active compound may be mammea E/BB. Extracts from M. siamensis flowers show promise as naturally occurring anti-cancer drugs.